Validation of monoplex assays detecting antibodies against Corynebacterium diphtheriae and Clostridium tetani toxins, rubella virus and parvovirus B19 for incorporation into Multiplex Serology - Brenner, Nicole; Tabatabai, Julia; Schnitzler, Paul (Methods, 2019)
Serological assays detecting antibodies in serum or plasma samples are useful and versatile instruments to investigate an individual’s infection and vaccination history, e.g. for clinical diagnosis, personal risk evaluation, and seroepidemiological studies. Multiplex Serology is a suspension bead array-based high-throughput methodology for simultaneous measurement of antibodies against multiple pathogens in a single reaction vessel, thus economizing sample volume, measurement time, and costs. We developed and validated bead-based pathogen-specific Monoplex Serology assays, i.e. assays including only antigens for the respective pathogen, to detect antibodies against Corynebacterium diphtheriae and Clostridium tetani toxins, rubella virus and parvovirus B19. The developed assays expand the portfolio of existing pathogen-specific bead-based serology assays and can be efficiently incorporated into larger Multiplex Serology panels. The newly developed Monoplex Serology assays consist of only one antigen per infectious agent, expressed as Glutathione S-transferase-fusion proteins in E. coli. Specificity, sensitivity and Cohen’s kappa statistics in comparison with routine clinical diagnostic assays were calculated for serum dilutions 1:100 and 1:1000. All pathogen-specific assays were successfully validated at both serum dilutions with the exception of rubella Monoplex Serology which showed impaired sensitivity (57.6%) at dilution 1:1000. Specificities of successfully validated Monoplex Serology assays ranged from 85.6% to 100.0% (median: 91.7%), and sensitivities from 81.3% to 95.8% (median: 90.9%); agreement with the reference assays ranged from substantial to almost perfect (kappa: 0.66–0.86, median: 0.78). Statistical performance and slim assay design enable efficient incorporation of the developed assays into Multiplex Serology.
Gesehen am 22.05.2019